AI-ENHANCED APPROACHES TO DEVELOPING ENGLISH SPEAKING SKILLS: APPLICATIONS OF TALKPAL AND KIALO EDU - Hotamova Iroda Ibrohimovna (Bright Mind Publishing, 2026)
This study investigates the application of artificial intelligence (AI) technologies in enhancing English speaking competence among higher education students. Two AI-driven platforms, TalkPal and Kialo Edu, were employed to strengthen oral communication, pronunciation, and critical thinking skills. TalkPal facilitates dialogue-based interactive exercises based on Communicative Language Teaching (CLT) and Task-Based Learning (TBL) principles, while Kialo Edu promotes structured debates and argumentation following Debating Method and Critical Thinking Pedagogy [1; 12–14 p.]. A 10-week independent learning intervention was conducted, with pre- and post-tests measuring pronunciation accuracy, lexical usage, and argumentative skills. Results indicate significant improvements across all indicators, demonstrating the effectiveness of AI-assisted platforms for independent and communicative English learning.
Keywords: Artificial Intelligence, English Speaking Skills, TalkPal, Kialo Edu, Communicative Language Teaching, Task-Based Learning, Critical Thinking, Debating Method, Independent Learning.